Experiência pedagógica pela linguagem poética e corporal - Maciel, Rochele Rita Andreazza (My University, 2014)
This work encompasses research done at Universidade de Caxias do Sul’s Post-Graduation Program (PPGEd-UCS), through its line of research Education, Language and Technology, and its focus is the study of poetic and body language in the pedagogical educational experience. With the aim of looking for contributions in this line of research to the theme chosen, this study suggests the following problem for discussion: “Which relationships young children of first years of primary school establish between body and poetry, from experiencing a learning project involving recreational activities, and how these relationships contribute for their process of teaching/learning?” It is organized in four chapters: chapter 1- Base of the landscape of the four seasons: child, language and learning; Chapter 2- Methodological traces of four season’s landscape; Chapter 3- Appreciation of the collected elements of the landscape of the four seasons; Chapter 4: Combination of elements in the constitution of the four seasons’ landscape. Studies used as reference include Ariès (1981); Bordini (1991); Dewey (1959; 1971; 1980); Huizinga (2000); Hauser (1977); Jolibert (1994); Merleau-Ponty (1999); Ostrower (1987); Paviani (2008; 2009); Ramos (2006; 2010); Santin (1987; 1990; 1994); Vygotsky (1998; 2000), among others. The method used in this piece of research was the qualitative approach, together with action research principles, in the context of private school, in a group of 10 (ten) children, aged between six and nine years old. Through an extra-curricular project, in the modality “full-time”, a piece of research on literary text reading was created and implemented. It was named “Abrapalavra”. This proposal focused literary reading of poems, from pedagogic actions in which recreation predominated, in planned and mediated actions that emphasized games/playing, through body movement and group regular contact. In this sense, a specific cut off is presented about the relationship that contains different dimensions of poetic and body language, through the learning project “We are poetic body”. From this project, fifteen classes were done, where recreational activities were emphasized, with the aim of promoting reading of the poetic text associated to body. For analysis, three thematic axis were created: (1) Reading of reality: the first relationships of recreational activities involving poetry in the body. (2º) Relations established in the recreational activities involving poetry in the body; - From the action of thinking to the action of doing, in different pedagogic moments; - From thinking and doing to the action of reflecting;- From thinking, doing and reflecting to the action of poetic creativity in language; (3º) Architectural relationships, at the end of the project, in the recreational activities involving poetry in the body. The analysis of the constructed data shows that poetic reading is important to build identity of the subjects, integrating different dimensions of language and making note that it is possible to learn interlinked knowledge to our way of thinking, acting, feeeling and expressing ourselves. Thus, the applied learning project achieves the proposed objectives and points at the relevance of inserting significative elements in extra-curricular projects, for pedagogic actions directed to the process of teaching-learning, as planning, enhancement of children’s experience and interdisciplinarity. That's why it is affirmed that dimensions of poetic and body language may be related to each other and, thus, may qualificate the educative process at school and in life.
Esta dissertação contempla pesquisa realizada no Programa de Pós-Graduação da Universidade de Caxias do Sul (PPGEd- UCS), através da Linha de Pesquisa Educação, Linguagem e Tecnologia e tem como foco o estudo da linguagem poética e corporal, na experiência pedagógica educacional. Com a intenção de buscar contribuições nessa linha de pesquisa à temática eleita, o estudo propõe a discussão do problema: “Que relações as crianças dos anos iniciais do Ensino Fundamental estabelecem entre poesia e corpo, a partir da vivência de projeto de aprendizagem envolvendo atividades lúdicas, e de que forma tais relações contribuem para seu processo de ensino-aprendizagem?” A dissertação está organizada em quatro capítulos, sendo o capítulo 1 – Alicerce da paisagem das quatro estações: a criança, a linguagem e a aprendizagem; o capítulo 2 – Traços metodológicos da paisagem das quatro estações; o capítulo 3 – Apreciação dos elementos coletados da paisagem das quatro estações; e o capítulo 4 – Combinação dos elementos na constituição da paisagem das quatro estações. Utilizaram-se como referenciais estudos de Ariès (1981); Bordini (1991); Dewey (1959; 1971; 1980); Huizinga (2000); Hauser (1977); Jolibert (1994); Merleau-Ponty (1999); Ostrower (1987); Paviani (2008; 2009); Ramos (2006; 2010); Santin (1987; 1990; 1994); Vygotsky (1998; 2000), entre outros. O método utilizado na pesquisa foi de enfoque qualitativo, acompanhado dos princípios de pesquisa-ação, no contexto de escola privada, em um grupo de 10(dez) crianças de turma multisseriada, com idades entre seis e nove anos. Através de um projeto extracurricular, na modalidade Tempo Integral, criou-se e implantou-se um projeto de pesquisa de leitura de texto literário, chamado “Abrapalavra”. A proposta enfocou a leitura literária de poemas, a partir de ações pedagógicas nas quais predominou a ludicidade, em ações planejadas e mediadas que priorizaram o jogo/a brincadeira, a exploração do corpo e a convivência em grupo. Nesse sentido, apresenta-se um recorte específico da relação que abrange diferentes dimensões da linguagem poética e corporal, através do projeto de aprendizagem “Somos corpo poético”. A partir daí, foram realizados quinze encontros nos quais predominaram atividades lúdicas, a fim de promover a leitura do texto poético associada ao corpo. Toma-se, para análise, a criação de três eixos temáticos: (1º) Leitura da realidade: as primeiras relações das atividades lúdicas envolvendo poesia no corpo. (2º) Relações estabelecidas nas atividades lúdicas envolvendo poesia no corpo; - Da ação de pensar à ação de fazer, nos diferentes momentos pedagógicos; - Do pensar e fazer à ação de refletir;- Do pensar, fazer e refletir à ação da criação poética na linguagem; (3º) Relações arquitetônicas, ao término do projeto, nas atividades lúdicas envolvendo poesia no corpo. A análise dos dados construídos evidencia que a leitura poética é importante para a construção da identidade dos sujeitos, integrando diferentes dimensões da linguagem e fazendo perceber que se podem aprender conhecimentos entrelaçados a nossa forma de pensar, de agir, de sentir, de se expressar. Assim, o projeto de aprendizagem aplicado atinge os objetivos propostos e aponta para a relevância de inserir, nos projetos extracurriculares, elementos significativos para as ações pedagógicas voltadas ao processo ensino-aprendizagem, tais como planejamento, valorização da experiência das crianças e interdisciplinaridade. Por isso, afirma-se que as dimensões da linguagem poética e corporal podem-se relacionar e qualificar o processo educativo na escola e na vida.
Keywords: Aprendizagem; Linguagem poética; Educação; Language; Poetry